Synthesis and Reactivity of Donor‐Stabilized Bis(pentafluoroethyl)stannylene [Sn(C2F5)2(D)n] (D=THF, DMAP, PMe3, [Sn(C2F5)3]−). Issue 17 (23rd February 2018) - Klösener, Johannes; Wiesemann, Markus; Niemann, Mark; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract: In this contribution we report on the synthesis of bis(pentafluoroethyl)stannane, H2 Sn(C2 F5 )2 . In the reaction with donor molecules a ready elimination of hydrogen and the formation of the corresponding donor‐stabilized monomeric bis(pentafluoroethyl)stannylene, Sn(C2 F5 )2, becomes apparent. With dependence on the Lewis basicity and steric demand of the donor, varying coordination numbers are realized. Whereas the reaction with nitrogen bases like 4‐(dimethylamino)pyridine (DMAP) leads to the complexation of two donor molecules, [Sn(C2 F5 )2 (dmap)2 ], treatment with PMe3 or [Sn(C2 F5 )3 ] − furnished the corresponding neutral or anionic monoadducts, [Sn(C2 F5 )2 (D)] (D=PMe3, [Sn(C2 F5 )3 ] − ). In contrast, the utilization of sterically demanding donors, such as i Pr2 O, as well as the thermal treatment of ether complexes, [Sn(C2 F5 )2 (D) n ] (D=Et2 O, THF), leads to the formation of oligomeric and cyclic stannylene moieties [Sn(C2 F5 )2 ] n . The reactivity of H2 Sn(C2 F5 )2 and the donor‐stabilized stannylenes was proven by hydrostannylation and complexation reactions with tetracarbonylnickel and bimetallic compounds. In the latter case, a donor‐dependent stannylene or distannylene insertion into the metal–metal bond was observed. Abstract : Sn(C2 F5 )2 exists in the complexed monomeric form [Sn(C2 F5 )2 (D) n ] (D=THF, 4‐(dimethylamino)pyridine (DMAP), PMe3, [Sn(C2 F5 )3 ] − ), whereas under donor‐free conditions the formation of oligomeric and cyclic stannylenes becomes apparent. In reactions with bimetallic compounds, a donor‐dependent stannylene or distannylene insertion into metal–metal bonds is observed (see scheme).